Dicopper(II) Metallacyclophanes with Electroswitchable Polymethyl‐Substituted para‐Phenylene Spacers. Issue 36 (22nd July 2013) - Ferrando‐Soria, Jesús; Castellano, María; Ruiz‐García, Rafael; Cano, Joan; Julve, Miguel; Lloret, Francesc; Ruiz‐Pérez, Catalina; Pasán, Jorge; Cañadillas‐Delgado, Laura; Armentano, Donatella; Journaux , Yves; Pardo, Emilio
Abstract Double‐stranded anionic dinuclear copper(II) metallacyclic complexes of the paracyclophane type [Cu2L2]4− have been prepared by the CuII‐mediated self‐assembly of different para‐phenylenebis(oxamato) bridging ligands with either zero‐, one‐, or four‐electron‐donating methyl substituents (L=N, N′‐para‐phenylenebis(oxamate) (ppba; 1), 2‐methyl‐ N, N′‐para‐phenylenebis(oxamate) (Meppba; 2), and 2, 3, 5, 6‐tetramethyl‐ N, N′‐para‐phenylenebis(oxamate) (Me4ppba; 3)). These complexes have been isolated as their tetra‐n‐butylammonium (1 a–3 a), lithium(I) (1 b–3 b), and tetraphenylphosphonium salts (1 c–3 c). The X‐ray crystal structures of 1 a and 3 c show a parallel‐displaced π‐stacked conformation with a smaller deviation from perpendicularity between the two benzene rings and the basal planes of the square planar CuII ions when increasing the number of methyl substituents (average dihedral angles (ϕ) of 58.72(7) and 73.67(5)° for 1 a and 3 c, respectively). Variable‐temperature (2.0–300 K) magnetic‐susceptibility measurements show an overall increase of the intramolecular antiferromagnetic coupling with the number of methyl substituents onto the para‐phenylene spacers (−J=75–95, 100–124, and 128–144 cm−1 for 1 a–c, 2 a–c, and 3 a–c, respectively; H=−JS1×S2). Cyclic voltammetry (CV) measurements show a reversible one‐electron oxidation of the double polymethyl‐substituted para‐phenylenediamidate bridging skeleton at a relatively low formal potential that decreases with the number of methyl substituents (E1=+0.33, +0.24, and +0.15 V vs. SCE for 1–3, respectively). The monooxidized dicopper(II) π‐radical cation species 3′ prepared by the chemical oxidation of 3 with bromine exhibits intense metal‐to‐ligand charge‐transfer (MLCT) transitions in the visible and near‐IR (λmax=595 and 875 nm, respectively) regions together with a rhombic EPR signal with a seven‐line splitting pattern due to hyperfine coupling with the nuclear spin of the two CuII ions. Density functional (DF) calculations for 3′ evidence a characteristic iminoquinonoid‐type short‐long‐short alternating sequence of CN and CC bonds for both tetramethyl‐para‐phenylenediamidate bridges and a large amount of spin density of negative sign mainly delocalized along each of the four benzene C atoms directly attached to the amidate N atoms, which is in agreement with a fully delocalized π‐stacked monoradical ligand description. Hence, the spins of the two CuII ions (SCu=1/2) that are antiparallel aligned in 3 (OFF state) become parallel in 3′ (ON state). Further developments may be then envisaged for this new permethylated dicopper(II) paracyclophane with a redox noninnocent ligand as a prototype for molecular magnetic electroswitch.